The new good life : living better than ever in an age of less - Robbins, John. (New York : Ballantine Books, 2010)
Provides a philosophical and prescriptive path from conspicuous consumption to conscious consumption. Where the old view of success was measured by cash, stocks, and luxuries, the new view will be guided by financial restraint and a new awareness of what truly matters. A passionate manifesto on finding meaning beyond money and status, this book delivers a sound blueprint for living well on less--everything you need to develop high-joy, low-cost solutions to life's challenges.--From publisher description.
Includes bibliographical references and index.
Keywords: Thriftiness; Finance, Personal; Money -- Psychological aspects